Saudi K-12 teachers' views on English teaching using technology - Al-alami, Aisha Mohammed; Alhamami, Munassir (Universitas Muhammadiyah Malang, 2024)
Teachers play a vital role as key stakeholders in the educational process. They have comprehensive insights into specific challenges that schools encounter, and their perspectives can provide in-depth presentations on particular issues faced within schools. This study investigated the perceptions of Saudi K-12 teachers on the use of technologies in teaching English as a foreign language (EFL). A mixed-method study was conducted in 13 K-12 schools in the southern part of Saudi Arabia to investigate teachers' perceptions of using technologies in teaching and learning EFL. The study involved 35 teachers, both male and female, who teach English at different levels in K-12 education. Quantitative data were collected through questionnaires (n = 30) and analyzed quantitatively. Qualitative data were collected through interviews (n = 5) and analyzed thematically. The study found that Saudi K-12 teachers generally have positive perceptions of the use of technologies to teach English in their classrooms. They believe that technologies can improve student motivation, engagement, and achievement. They also believe that technologies can give students access to a wider range of resources and help them develop 21st-century skills. The study also identified some challenges to the use of technologies in Saudi K-12 education, such as lack of teacher training, limited access to technology, and cultural factors. However, the study also provided valuable insights into the criteria that teachers use to choose technologies to teach English in Saudi Arabia. The findings of this study have implications for the development of technology policies and practices in K-12 schools. The findings also provide valuable insights for teachers and researchers who are interested in the use of technologies in EFL in general and K-12 education in particular.